1997
DOI: 10.1287/mksc.16.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Bias and Systematic Change in the Parameter Estimates of Macro-Level Diffusion Models

Abstract: Studies estimating the Bass model and other macra-leveldiffusion models with an unknown ceiling feature three curious empirical regularities: (i) the estimated ceiling is often close to the cumulative number of adopters in the last observation period, (ii) the estimated coefficient of social contagion or imitation tends to decrease as one adds later observations to the data set, and (iii) the estimated coefficient of social contagion or imitation tends to decrease systematically as the estimated ceiling increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(65 citation statements)
references
References 47 publications
(23 reference statements)
6
56
1
2
Order By: Relevance
“…The estimated market size parameter is quite close to the cumulative sales at the end of the last period (about 45 million units). This property of the model has been discussed elsewhere (e.g., Van den Bulte and Lilien, 1997;Venkatesan et al, 2003). Moreover, it is smaller in magnitude compared to that estimated for the proposed model (although, since the standard errors are large, the difference is not statistically significant).…”
Section: Bass Model Hazardmentioning
confidence: 50%
“…The estimated market size parameter is quite close to the cumulative sales at the end of the last period (about 45 million units). This property of the model has been discussed elsewhere (e.g., Van den Bulte and Lilien, 1997;Venkatesan et al, 2003). Moreover, it is smaller in magnitude compared to that estimated for the proposed model (although, since the standard errors are large, the difference is not statistically significant).…”
Section: Bass Model Hazardmentioning
confidence: 50%
“…Norton and Bass (1987) use the same innovation and imitation parameters to fit the diffusion data of different generations of DRAM. However, van den Bulte and Lilien (1997) point out that this model does not account for the decline of real prices, improving product performance, and increasing distribution penetration. These factors increase the total adopters and result in a downward pressure on the estimates (i.e., ψ and φ).…”
Section: Expansionmentioning
confidence: 99%
“…Estimation with larger data sets is via maximum likelihood or nonlinear least squares (NLS). The influential Marketing Science paper of Van den Bulte and Lilien (1997) established bias in the parameter estimates and concluded that an accurate estimate of the diffusion path and 'ultimate market size . .…”
Section: New-product Modelsmentioning
confidence: 99%